Analysis of a Scalable Multi-Projector System for Virtual Reality Environments - Teubl, Fernando; Cabral, Marcio; Zuffo, Marcelo; Kurashima, Celso (International Journal of Virtual Reality, 2013)
Virtual reality environments with multi-projector systems provide better visual quality, higher resolution and more brightness than traditional single-projector systems. Moreover, using multiple low-cost projectors is economically advantageous in comparison to an expensive high-end projector for equivalent visual performance. This article presents the research and development of a scalable multiprojection system that enables the construction of virtual reality systems with a large number of projectors and graphics computers, and that is capable of achieving a high resolution display. We demonstrate the viability of such system with the development of a camera-based multiprojector system library called FastFusion, which automatically calibrates casually aligned projectors to properly blend different projections. Our system software improves known algorithms in the literature for projector calibration and image blending. As a result, FastFusion improves system scalability and calibration reliability. In a detailed analysis of the visual performance of FastFusion in a CAVE system with three walls, eighteen projectors and nine computers, we achieved a satisfactory result for variance in geometric calibration and for graphics performance. Thus, our library is suitable for building complex projector systems and with retina resolution.